Politics and the Slavic languages - Kamusella, Tomasz, author.
1 online resource.
Keywords: "During the last two centuries, ethnolinguistic nationalism has been the norm of nation and state-building in central Europe. In the current age of borderless cyberspace, regional and minority Slavic languages are freely standardized and used, even when not officially recognized. As a result, the number of Slavic languages has varied widely from a single Slavic language to as many as 40. This timely book illustrates that decisions on what counts as a language are neither permanent nor stable, arguing that the politics of language equates politics in central Europe. It is an essential resource for scholars of linguistics and politics in Central Europe"--